The Relationship between Demographic Status and Comorbid Disease with the Risk of Chronic Kidney Disease in the Cut Meutia Hospital, Aceh Utara Regency - Anita Marlina; Said Usman; Yusni Yusni; Maimun Syukri; Hanifa Yusuf (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research aims to analyze the risk factors associated of Chronic Kidney Disease (CKD). This research was conducted in Rumah Sakit Umum Cut Meutia (RSUCM) North Aceh. Based on the Law of the Republic of Indonesia No. 39 Year 2009 regarding the prevention and control of disease not contagious is an attempt to improve the health of the community through activities promotive and preventive. This research is a cross sectional analytic research with a retrospective approach, this research is by searching the previous data. The data used in this study are secondary data at Rumah Sakit Umum Cut Meutia (RSUCM), North Aceh Regency in 2019, which aims to analyze risk factors associated with Chronic Kidney Disease (CKD). This research was conducted at Rumah Sakit Umum Cut Meutia (RSUCM), North Aceh District from 8 to 9 June 2020. The population included in this study were all patients with chronic kidney disease who received treatment at the Cut Meutia General Hospital in North Aceh Regency for the period January - December 2019 as many as 640 people.There is a relationship between the status of the demographics on the gender with risk the occurrence of disease chronic kidney where p value 0,452. There is relationship between disease comorbid in hypertension with the risk of the occurrence of disease chronic kidney where p value by 0,000. The relationship between disease comorbid in diabetes risk the occurrence of disease chronic kidney where p value by 0,000.